2023
DOI: 10.1186/s13018-023-03924-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perioperative tranexamic acid (TXA) in patients with calcaneal fractures: a meta-analysis and systematic review of randomized controlled trials

Abstract: Background Calcaneal fractures are a common orthopedic disease, account for approximately 2% of all bone fractures, and represent 60% of fractures of tarsal bones. Tranexamic acid (TXA) is a synthetic antifibrinolytic drug that competitively blocks the lysine-binding sites of plasminogen, plasmin, and tissue plasminogen activator, delaying fibrinolysis and blood clot degradation. However, the effect of TXA on patients with calcaneal surgery remains controversial. Our objective was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, the application of TXA in foot and ankle surgery is relatively rare [ 30 , 31 ]. Currently, few studies have shown that TXA has potential benefits in reducing blood loss and wound complications without increasing the risk of thromboembolic events [ 32 – 34 ], but there is still some controversy [ 35 , 36 ]. The foot and ankle are naturally poor in soft tissue, and soft tissue complications often occur after surgery, such as poor incision healing, incision infection or deep infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of TXA in foot and ankle surgery is relatively rare [ 30 , 31 ]. Currently, few studies have shown that TXA has potential benefits in reducing blood loss and wound complications without increasing the risk of thromboembolic events [ 32 – 34 ], but there is still some controversy [ 35 , 36 ]. The foot and ankle are naturally poor in soft tissue, and soft tissue complications often occur after surgery, such as poor incision healing, incision infection or deep infection.…”
Section: Discussionmentioning
confidence: 99%